FTO Knockout Causes Chromosome Instability and G2/M Arrest in Mouse GC-1 Cells - Huang, Tao; Gao, Qiang; Feng, Tongying; Zheng, Yi; Guo, Jiayin; Zeng, Wenxian (Frontiers in Genetics, 2019)
N6-methyladenosine (m6A) is the most abundant modification on eukaryotic mRNA. m6A plays important roles in the regulation of post-transcriptional RNA splicing, translation and degradation. Increasing studies have uncovered the significance of m6A in various biological processes such as stem cell fate determination, carcinogenesis, adipogenesis and stress response, which put forward a novel conception called epitranscriptome. However, functions of the fat mass and obesity associated protein (FTO), the first characterized m6A demethylase, in spermatogenesis remains obscure. Here we reported that depletion of FTO by CRISPR/Cas9 induces chromosome instability and G2/M arrest in mouse spermatogonia, which was partially rescued by expression of wild type FTO but not demethylase inactivated FTO. FTO depletion significantly decreased the expression of mitotic checkpoint complex and G2/M regulators. We further demonstrated that the m6A modification on Mad1, Mad2, Bub1b, Cdk1 and Ccnb2 were directly targeted by FTO. Therefore, FTO regulates cell cycle and mitosis checkpoint in spermatogonia because of its m6A demethylase activity. The findings give novel insights into the role of RNA methylation in spermatogenesis.